CURRENT ENGLISH LOANWORDS IN THE COMMUNICATIVE PRACTICE OF YOUTH SUBCULTURE - Laylo Sunnatova (Modern American Journals, 2025)
The article addresses a pressing linguistic issue – the borrowing of foreign language concepts in the context of youth speech practices. In the era of the Internet’s active functioning and the growing influence of mass media (television programs, glossy magazines, blogs), there is an intensive influx of foreign lexical units, particularly Anglicisms, into the Russian language. Special attention is given to the reasons for using borrowed words despite the availability of synonymous expressions in Russian, as well as to the mechanisms of their consolidation and development in everyday communication. The article examines the semantic features of Anglicisms, their transformation, and the processes of adaptation within the Russian-speaking environment. The article also presents the results of a sociolinguistic study conducted among university students, which revealed the degree of prevalence of foreign words in their speech and helped identify the most common, rare, and controversial borrowings. In addition, the study analyzes possible reasons behind the choice of certain terms and explores options for replacing them with Russian lexical equivalents.
Keywords: Lexical borrowings, Anglicisms, foreign language concepts, youth language, slang.